Pemanfaatan Media Cetak dan Sosial untuk Meningkatkan Literasi dan Numerasi Siswa di Desa Namanjahe - Jen Agus Perry Hasibuan; Abu Yazid Raisal (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research aims to improve students' literacy and numeracy skills in Namanjahe Village through the utilization of print and social media. The approach used is participatory action research, where researchers are directly involved in activities to address the educational challenges faced by students. Based on interviews and observations, several issues were identified, such as low literacy rates, limited use of educational technology, and a pragmatic mindset that hinders mathematical thinking. The action plan includes introducing print media and social media in classroom activities, demonstrating how to use blogs, creating engaging learning environments, and participating in religious education activities at TPQ Al-Hidayah. The results of the program show that the use of diverse media can stimulate student interest and help improve their literacy and numeracy skills. However, consistent support and follow-up are still needed to ensure long-term impacts on student learning outcomes.